1996
DOI: 10.1111/j.1476-5381.1996.tb15712.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in superoxide dismutase mRNA expression by streptozotocin‐induced diabetes

Abstract: Experiments were designed to investigate the involvement of superoxide anions in the attenuated endothelium‐dependent relaxation of the rat aorta from streptozotocin (STZ)‐induced diabetic rats. The endothelium‐dependent relaxation responses to acetylcholine (ACh, 10−7 m) in helical strips of the aorta precontracted with noradrenaline (NA, 5 × 10−8∼3 × 10−7 m) were significantly decreased in STZ‐induced diabetic rats. The recovery phase of the relaxation after single administration of ACh in the STZ‐induced di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 53 publications
3
62
0
Order By: Relevance
“…Our success in this regard is evidenced in the present study by the ®nding that a relaxation of over 80% of the noradrenaline-induced contraction was induced by as little as 10 77 M ACh ( Figure 1a). The reduced endothelium-dependent relaxation seen in diabetic rats in the present study is in agreement with the results of numerous other studies on aortae from STZinduced diabetic rats (Oyama et al, 1986;Kamata et al, 1989;Poston & Taylor, 1995;Pieper, 1998;Kamata & Kobayashi, 1996;Kobayashi & Kamata, 1999a, b;Kobayashi et al, 2000;De Vriese et al, 2000;Hink et al, 2001).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our success in this regard is evidenced in the present study by the ®nding that a relaxation of over 80% of the noradrenaline-induced contraction was induced by as little as 10 77 M ACh ( Figure 1a). The reduced endothelium-dependent relaxation seen in diabetic rats in the present study is in agreement with the results of numerous other studies on aortae from STZinduced diabetic rats (Oyama et al, 1986;Kamata et al, 1989;Poston & Taylor, 1995;Pieper, 1998;Kamata & Kobayashi, 1996;Kobayashi & Kamata, 1999a, b;Kobayashi et al, 2000;De Vriese et al, 2000;Hink et al, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…A considerable body of evidence now suggests that the impairment of endothelium-dependent relaxation seen in diabetes and atherosclerosis may involve inactivation of NO by oxygen-derived free radicals (Kamata & Kobayashi, 1996;Kobayashi & Kamata, 1999a;Meraji et al, 1987;Pieper et al, 1992;Hattori et al, 1991;Ooboshi et al, 1997;Lund et al, 1999;Pagano et al, 1998). Production of superoxide anion inactivates NO (Marshall et al, 1988;Rubanyi & Vanhoutte, 1986;Kobayashi & Kamata, 2001) and dismutation of free radicals has generally (Pieper et al, 1996;Hattori et al, 1991;Kamata & Kobayashi, 1996) but not always (Heygate et al, 1995) been found to improve impaired endothelium-dependent relaxation in experimental models of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the excessive elevations in plasma glucose, insulin, low density lipoprotein (LDL) cholesterol, endothelin-1 (ET-1), Ang II, and reactive oxygen species that occur in diabetes are involved in the development of this dysfunction in several blood vessels. Indeed, a considerable body of evidence now suggests that in type I diabetes, the observed impairment of endothelial function may involve inactivation of NO by oxygen-derived free radicals (Meraji et al, 1987;Hattori et al, 1991;Pieper et al, 1992;Tesfamariam, 1994;Keaney and Vita, 1995;Kamata et al, 1996a;Ooboshi et al, 1997;Kobayashi and Kamata, 1999a, 2002b. In experimental models of type I diabetes, an enhancement of NO production (which in such models is diminished by superoxide anion) and dismutation of free radicals has generally been found to improve impaired endothelium-dependent relaxation (Rubanyi and Vanhoutte, 1986;Marshall et al, 1988;Kobayashi and Kamata, 2001).…”
Section: Mechanisms Underlying Impaired Endothelial Function In Diabementioning
confidence: 99%